Factors Affecting Satisfaction Level of Leisure Tourists: Post Covid-19 Analysis - Low Teck En,; R. Chandrashekar, (Research in Management of Technology and Business, 2023)
The leisure tourism is one of the significant economies boosting sector due to which Malaysia has to earn incredible growth in the tourism sector worldwide. However, due to Covid-19 pandemic, the tourism industry had been affected and the number of tourists has plummeted drastically. This research is aim to identify the factors affecting the satisfaction levels of leisure tourist, identify the satisfaction levels of leisure tourist and examine the relationship between the factor and satisfaction level of leisure tourist. The research will apply quantitative research approach to conduct the questionnaire and distributed to 350 inbound ASEAN tourists that visit Kuala Lumpur. The study will apply convenience sampling to gather information. Statistical Package for Social Sciences (SPSS) will be used to examine the data in the questionnaire. The outcomes of this study are anticipated to give stakeholders and policymakers in the leisure tourism sectors with significant insights.